Comparison of Caudal Tramadol with different doses of Midazolam addon for Postoperative analgesia in Children Undergoing Inguinoscrotal Operations - Koirala, Siddhartha; Bhattarai, BK; Rahman, TR; Sah, BP (Journal of BP Koirala Institute of Health Sciences, 2019)
Background: Safe and effective postoperative analgesic modalities have remained a subject of contemporary clinical research, particularly in children. The present study aimed at comparing the effectiveness of pain relief in children undergoing inguinoscrotal surgery with caudal tramadol alone and in combination with different doses of midazolam. Methods: Ninety children of either sex, aged one year to fifteen years, undergoing inguinoscrotalsurgical procedures under general anesthesia were recruited in a randomized double blinded fashion to receive one of the three study medications through caudal route. Group T (n= 30) received injectiontramadol 2mg/kg in a volume of 0.5ml/kg up to a maximum volume of 20ml, while group TM (n= 30)and TM/2 (n= 30) received additional midazolam 50mcg/kg and 25mcg/kg respectively. The study medications were administered immediately after induction of anesthesia. Postoperative analgesia was measured using a modified Hannallah 10 points Pediatric Objective Pain Scale described by Hannallah and colleagues. Pain score of ≤ 4 was considered effective analgesia. Duration of analgesia was defined as the time between caudal injection to the first need of analgesia. Results: The duration of analgesia in group TM (1145±281.41 min) and TM/2 (1012.67±260.68 min)was significantly longer than that in group T (690.83±215.7 min) (p<0.005). The sedation score was the highest in group TM and the least in group T. Nausea vomiting was the commonest side effect in all the three groups without any significant differences in the incidences between the groups. Conclusion: Addition of midazolam to tramadol for caudal administration in children undergoinginguinoscrotal operations produces significantly longer duration of postoperative analgesia than produced by epidural administration of tramadol alone.